Remarks on Wire and Die Bonding for Hybrid Circuits. (1977) - Soffa, A.
Abstract : Advances in hybrid automatic wire bonding include refined joy stick techniques, automatic alignment, a digitally operated head for higher speeds and flexibility, missing ball detection and programming aids. Advanced hybrid die attach equipment will have to accept a large variety of chip presentation techniques but will use CCTV and automatic alignment with microprocessor controls to aid programming and speed output.